Bispecific antibodies tethering innate receptors induce human tolerant-dendritic cells and regulatory T cells - Lamendour, Lucille; Gilotin, Mäelle; Deluce-Kakwata Nkor, Nora; Lakhrif, Zineb; Meley, Daniel; Poupon, Anne; Laboute, Thibaut; di Tommaso, Anne; Pin, Jean-Jacques; Mulleman, Denis; Le Mélédo, Guillaume; Aubrey, Nicolas; et al. (Frontiers in Immunology, 2024)
There is an urgent need for alternative therapies targeting human dendritic cells (DCs) that could reverse inflammatory syndromes in many autoimmune and inflammatory diseases and organ transplantations. Here, we describe a bispecific antibody (bsAb) strategy tethering two pathogen-recognition receptors at the surface of human DCs. This cross-linking switches DCs into a tolerant profile able to induce regulatory T-cell differentiation. The bsAbs, not parental Abs, induced interleukin 10 and transforming growth factor β1 secretion in monocyte-derived DCs and human peripheral blood mononuclear cells. In addition, they induced interleukin 10 secretion by synovial fluid cells in rheumatoid arthritis and gout patients. This concept of bsAb-induced tethering of surface pathogen-recognition receptors switching cell properties opens a new therapeutic avenue for controlling inflammation and restoring immune tolerance.